Effective use of Microsoft Enterprise library : building blocks for creating enterprise applications and services - Fenster, Len (Microsoft .NET development series., 2006)
Writing robust enterprise applications presents a special challenge for developers, but Microsoft has addressed that challenge with the free, downloadable Enterprise Library for the .NET Framework. Enterprise Library is a collection of application blocks and guidance documents that together provide functionality common to enterprise applications; each application block includes full source code. Lacking in the guidance provided by Microsoft is an overall roadmap to the process of using the application blocks. Effective Use of Microsoft Enterprise Library is that roadmap. Microsoft application development lead architect Len Fenster explains exactly how to build applications using Enterprise Library application blocks. Fenster covers all seven application blocks as implemented for .NET Framework 1.1, shows how to develop and use a new application block, and explains how Enterprise Library is changing for .NET Framework 2.0. Readers will learn How the Configuration Application Block is designed and can be used at runtime to easily read and write configuration data How the Configuration Application Block works at design time for all blocks How to use the Data Access Block to create a portable data layer How to use the Exception Handling Application Block to implement a policy-driven, application-wide exception handling system How to use the Logging and Instrumentation Application Block to log and instrument messages independent of the message destination How to add authentication, authorization, role membership, security cache, and profile membership features to an application with the Security Application Block How to use the Cryptography Application Block to add functionality to encrypt and decrypt data and create and compare hashes How to build your own application block and providers that "snap" right into Enterprise Library Whether you plan to extend Enterprise Library for your organization, or just use the existing application blocks to add functionality to your architecture in a consistent, extensible, integrated way, this book will guide you through the complexities and help you find a clear path to success.